Wheat TaAS2, a member of LOB family, affects the adaxial-abaxial polarity of leaves in transgenic Arabidopsis - Ma, X.; Tao, Y.; Zhao, X.; Zhang, X.
Establishment of adaxial-abaxial polarity is very important to the pattern formation of leaves. Previous studies indicated that ASYMMETRIC LEAVES2 (AS2)in Arabidopsis is a critical gene that functions on the determination of adaxial-abaxial polarity. To understand the molecular mechanism of polarity establishment in wheat, a gene that shares higher homology with AS2 was isolated from wheat (Triticum aestivum L.)and it was designated as TaAS2. TaAS2 encoded a protein with a LOB-domain containing a C-motif and a leucine-zipper-like sequence and it was expressed throughout leaf primordia and prevascular tissues and vascular bundles. Ectopic expression of TaAS2 in Arabidopsis mainly resulted in the adaxialization of abaxial mesophyll tissues and the alteration of the vascular pattern in leaves and petioles. Further study showed that the expression of TaAS2 affected the transcript levels of several polarity genes and KNOX genes in Arabidopsis. Our results suggest that TaAS2 may play important roles in regulating plant development.
Keywords: ADAXIAL-ABAXIAL POLARITY; FUNCTIONAL ANALYSIS; GENE EXPRESSION; TAAS2 GENE; WHEAT